Adoption of spineless cactus pear by 7,000 smallholder farmers in Jordan and India as a multipurpose crop for enhanced resilience and increased household income - CGIAR Research Program on Livestock (2021)
Research, advocacy and trainings on spineless cactus pear (Opuntia Ficus-indica) across South and West Asia by ICARDA and partners has led to rapid adoption by smallholder farmers, who are benefiting from greater income. Government, NARS, NGOs, private sector and universities support for the crop are amplifying efforts. Consumer demand for cactus pear products in Jordan is on the rise and farmer appreciation of the crop in India has shifted. In both countries, demand for cladodes (leaf-like stems) have surpassed availability.